Linggui Zhugan Decoction activates the SIRT1-AMPK-PGC1α signaling pathway to improve mitochondrial and oxidative damage in rats with chronic heart failure caused by myocardial infarction - Siyi Yu; Siyi Yu; Hang Qian; Dawei Tian; Mingming Yang; Dongfeng Li; Hao Xu; Jishun Chen; Jingning Yang; Xincai Hao; Zhixin Liu; Jixin Zhong; et al. (Frontiers Media S.A., 2023)
Objective: To investigate the effects of Linggui Zhugan Decoction on mitochondrial and oxidative damage in rats with chronic heart failure after myocardial infarction and the related mechanisms.Methods: Chronic heart failure after myocardial infarction was established by coronary artery ligation. Heart failure rats were randomly divided into three groups: Model group (n = 11), Linggui Zhugan Decoction group (n = 12), and captopril group (n = 11). Rats whose coronary arteries were only threaded and not ligated were sham group (n = 11). Cardiac function, superoxide dismutase (SOD), malondialdehyde (MDA) contents, soluble growth-stimulating expression factor (ST2), and N-terminal B-type brain natriuretic peptide precursor (NTproBNP) levels were analyzed after treatment. Moreover, the level of mitochondrial membrane potential was detected by JC-1 staining, the ultrastructural of myocardial mitochondria were observed by transmission electron microscopy. The related signal pathway of silent information regulator factor 2-related enzyme 1 (SIRT1), adenylate activated protein kinase (AMPK), phosphorylated adenylate activated protein kinase (p-AMPK), and peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) is an important pathway to regulate mitochondrial energy metabolism, and to initiate mitochondrial biogenesis. The expression level was detected by Western blot and reverse transcription to explore the mechanism of the decoction.Results: Compared with the model rats, Linggui Zhugan Decoction significantly improved cardiac function (p < 0.05), reduced MDA production (p < 0.01), increased SOD activity (p < 0.05), reduced ST-2(p < 0.01), and NT-proBNP(p < 0.05) levels, increased mitochondrial membrane potential, and improved mitochondria function. In addition, Linggui Zhugan Decoction upregulated the expression of SIRT1, p-AMPK, PGC-1α protein, and mRNA in cardiac myocytes.Conclusion: Linggui Zhugan Decoction can improve the cardiac function of heart failure rats by enhancing myocardial antioxidant capacity and protecting the mitochondrial function, the mechanism is related to activating SIRT1/AMPK/PGC-1α signaling pathway.